2012
DOI: 10.1080/15381501.2012.652539
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term HIV/AIDS Survivors: Coping Strategies and Challenges

Abstract: The purpose of this qualitative study was to develop a clearer understanding of the challenges and needs of long-term HIV=AIDS survivors living in rural and semirural areas, as well as to explore what factors and resources may be related to more effective coping. Eleven long-term HIV=AIDS survivors were invited to participate in this research through an AIDS service organization working in rural= semirural California towns. Each participant was interviewed using structured questions. The interviews were transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In particular, despite solid commitment to their HIV medications, the overwhelmingly positive responses from the interviewees about the SMS reminder campaign highlight the intervention's broader impact beyond HIV medication adherence. Therefore, this study underscores the urgency to shift the much compartmentalised focus on ART adherence support alone to the much neglected synergy between chronic disease self-management and stigma reduction (Gannon & Stacciarini, 2016;Grov et al, 2010;Katz et al, 2013;Sankar et al, 2011;Stowers Johansen & Kohli, 2012).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In particular, despite solid commitment to their HIV medications, the overwhelmingly positive responses from the interviewees about the SMS reminder campaign highlight the intervention's broader impact beyond HIV medication adherence. Therefore, this study underscores the urgency to shift the much compartmentalised focus on ART adherence support alone to the much neglected synergy between chronic disease self-management and stigma reduction (Gannon & Stacciarini, 2016;Grov et al, 2010;Katz et al, 2013;Sankar et al, 2011;Stowers Johansen & Kohli, 2012).…”
Section: Discussionmentioning
confidence: 86%
“…Issues broader than HIV were frequently raised in the interviews, including stigma and discrimination from a range of sources, loneliness resulting from social isolation and exclusion, recurrent depression, ageing and multiple HIV‐ and non‐HIV‐related disabilities. These are commonly reported experiences by older people with HIV and those who have lived with HIV for a long time (Grov, Golub, Parsons, Brennan, & Karpiak, ; Sankar, Nevedal, Neufeld, Berry, & Luborsky, ; Stowers Johansen & Kohli, ). Although most felt greatly supported by their medical care teams, the daily task of taking medication was a solitary responsibility, with the exception of one participant (Group 2, P10, age 63) who received help with his dosing regimen from his personal carer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coping is an important concept in the field of chronic illness as it allows health-care practitioners to gauge the impact of a disease on patients. For this reason, coping has been investigated in relation to a number of chronic illnesses such as HIV (Stowers Johansen and Kohli, 2012), diabetes (Collins et al, 2009), coeliac disease (Jacobsson et al, 2012) and rheumatoid arthritis (Ramjeet et al, 2008). Among women, coping research has extended to areas such as coping with infertility (Lee et al, 2010), ovarian cancer (Price et al, 2013) and polycystic ovary syndrome (PCOS) (Benson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence has suggested that social support is beneficial for health (Cohen & Janicki-Deverts, 2009). In particular, positive coping by PLWH has been associated with good social support (Stowers-Johansen & Kohli, 2012).…”
Section: Caregiving and Social Supportmentioning
confidence: 99%